Transformasi Pendidikan Pondok Pesantren Hasan Jufri Sangkapura Bawean Gresik - Mahfud, Mahfud (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2014)
This study tries to examine the transformation of education in Islamic BoardingSchool of Hasan Jufri, Sangkapura, Bawean, Gresik. The results of this study revealthat the role of Kiai’s leadership is very significant in education transformation.To respond to the contemporary challenges, Kiai conducts the process oftransformation by establishing a formal education institution. In addition, theprocess of transformation also requires the transformation of educational systemsamong such as redefining goals, curriculum, methods, as well as providing thenecessary facilities. However, the educational transformation held in IslamicBoarding School of Hasan Jufri also brings about some implications, both negativeand positive. The positive implication is that the quality of education has increasedsignificantly, while its negative implication is that some students tend to behaveunfavorably, such as undermining some religious norms and imitating urban lifestyles.